2020
DOI: 10.1016/j.cognition.2020.104375
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian or biased? Analytic thinking and political belief updating

Abstract: A surprising finding from U.S. opinion surveys is that political disagreements tend to be greatest among the most cognitively sophisticated opposing partisans. Recent experiments suggest a hypothesis that could explain this pattern: cognitive sophistication magnifies politically biased processing of new information. However, the designs of these experiments tend to contain several limitations that complicate their support for this hypothesis. In particular, they tend to (i) focus on people's worldviews and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 73 publications
4
59
0
Order By: Relevance
“…examining the role of numeracy), our data show that the ability to understand and reason with numbers is associated with decreased bias. Thus, our results are in line with previous studies suggesting that numeracy can lead to better decisions even in the context of highly politicized issues ( Connor et al, 2020 ; Lind et al, 2018 ; Tappin et al, 2020a )—and contradict those studies which have found increased motivated reasoning among highly numerate people ( Drummond and Fischhoff, 2017 ; Kahan et al, 2012 , 2017a , 2017b ; Nurse and Grant, 2020 ). This study revealed two more interesting findings concerning numeracy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…examining the role of numeracy), our data show that the ability to understand and reason with numbers is associated with decreased bias. Thus, our results are in line with previous studies suggesting that numeracy can lead to better decisions even in the context of highly politicized issues ( Connor et al, 2020 ; Lind et al, 2018 ; Tappin et al, 2020a )—and contradict those studies which have found increased motivated reasoning among highly numerate people ( Drummond and Fischhoff, 2017 ; Kahan et al, 2012 , 2017a , 2017b ; Nurse and Grant, 2020 ). This study revealed two more interesting findings concerning numeracy.…”
Section: Discussionsupporting
confidence: 75%
“…This finding, which may seem counterintuitive at first, is explained by the idea that highly numerate people can use their skills to rationalize their interpretations of existing evidence so that they align with their attitudes. Note, however, that not all studies that investigated motivated reasoning in the context of politically polarizing issues found such an effect ( Connor et al, 2020 ; Lind et al, 2018 ; Persson et al, 2021 ; Tappin et al, 2020a ). Thus, the relationship between numeracy and the degree of motivated reasoning may depend on various contextual factors.…”
mentioning
confidence: 94%
“…What this indicates is that effects that appear to be due to motivated reasoning (e.g., the interaction between cognitive sophistication and ideology in the prediction of climate change beliefs) are not attributable to differences in reasoning per se, but rather to differences in motivations among high-and low-skill reasoners. The apparent association between polarization and cognitive sophistication when people are evaluating climate change arguments under standard instructions may simply be due to people who are higher in sophistication being more engaged with the task (i.e., more motivated), or perhaps having stronger prior beliefs (Bago et al, 2020;Tappin, Pennycook, & Rand, 2020;Tappin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…But they found that higher CRT scores correlate with correctly rating fake news as less accurate and genuine news stories as more accurate, regardless of its fit with political leanings. In further work, the same group of researchers provide evidence that higher CRT scores are associated with updating of beliefs about factual political statements closer to Bayesian norms (Tappin et al, 2020a). The focus on belief updating is an important innovation because a shortcoming of other study designs is that they do not disentangle political identities from pre-treatment information exposure and issue-specific prior beliefs (Tappin et al, 2020b) A potential worry for this rival to Kahan's view can be motivated by other work by the very same group of researchers.…”
Section: Why Do People Believe Fake News?mentioning
confidence: 92%